Functionally Distinctive Ptch Receptors Establish Multimodal Hedgehog Signaling in the Tooth Epithelial Stem Cell Niche. (10th June 2019) - Binder, Martin; Chmielarz, Piotr; Mckinnon, Peter J.; Biggs, Leah C.; Thesleff, Irma; Balic, Anamaria
Abstract: Continuous growth of the mouse incisor teeth is due to the life-long maintenance of epithelial stem cells (SCs) in their niche called cervical loop (CL). Several signaling factors regulate SC maintenance and/or their differentiation to achieve organ homeostasis. Previous studies indicated that Hedgehog signaling is crucial for both the maintenance of the SCs in the niche, as well as for their differentiation. How Hedgehog signaling regulates these two opposing cellular behaviors within the confinement of the CL remains elusive. In this study, we used in vitro organ and cell cultures to pharmacologically attenuate Hedgehog signaling. We analyzed expression of various genes expressed in the SC niche to determine the effect of altered Hedgehog signaling on the cellular hierarchy within the niche. These genes include markers of SCs (Sox2 and Lgr5) and transit-amplifying cells (P-cadherin, Sonic Hedgehog, and Yap). Our results show that Hedgehog signaling is a critical survival factor for SCs in the niche, and that the architecture and the diversity of the SC niche are regulated by multiple Hedgehog ligands. We demonstrated the presence of an additional Hedgehog ligand, nerve-derived Desert Hedgehog, secreted in the proximity of the CL. In addition, we provide evidence that Hedgehog receptors Ptch1 and Ptch2 elicit independent responses, which enable multimodal Hedgehog signaling to simultaneously regulate SC maintenance and differentiation. Our study indicates that the cellular hierarchy in the continuously growing incisor is a result of complex interplay of two Hedgehog ligands with functionally distinct Ptch receptors. Stem Cells   2019;37:1238–1248 : Abstract : Sox2+ stem cells express Ptch1 and Ptch2 receptors, and are located in a region of high Hedgehog signaling pathway activity, mediated by two Hedgehog ligands: Sonic Hedgehog and Desert Hedgehog. Loss of Ptch1 receptor results in loss of Sox2 expression and differentiation of stem cells into early progeny. Advent of transit-amplifying cells from early progeny is marked by initiation of P-cadherin expression, triggered by BMP4-mediated inhibition of Hedgehog signaling. Exit of transit-amplifying cells and their commitment to ameloblast lineage is characterized by a loss of P-cadherin expression.